Pengaruh Persepsi Dukungan Organisasi Terhadap Kinerja Karyawan Dengan Kebahagiaan Di Tempat Kerja Sebagai Variabel Mediasi: Studi Pada Karyawan BPKP Provinsi Jawa Tengah - Salwa Sekar Ningtyas; Eisha Lataruva (Faculty of Economics and Business Diponegoro University, 2025)
Employee performance plays a vital role in achieving organizational success. One promising approach to improving performance is through enhancing perceived organizational support, which reflects the extent to which employees feel valued and supported by their organization. This study aims to analyze the effect of perceived organizational support on employee performance with happiness at work as a mediating variable. The research was conducted on employees of the Financial and Development Supervisory Agency of Central Java Province with a total of 90 respondents. A quantitative method was applied using Structural Equation Modeling-Partial Least Squares 4.0 (SEM-PLS). The result indicate that perceived organizational support has a positive and significant effect on employee performance. Furthermore, happiness at work is proven to mediate the relationship between perceived organizational support and employee performance. These findings highlight the importance of organizational attention not only to instrumental support but also to the psychological and emotional aspects experienced by employees. Organizations that foster a positive work environment and enhance emotional well-being are more likely to drive optimal performance.